2000
DOI: 10.1093/ps/79.7.961
|View full text |Cite
|
Sign up to set email alerts
|

Human Requirement for N-3 Polyunsaturated Fatty Acids

Abstract: The diet of our ancestors was less dense in calories, being higher in fiber, rich in fruits, vegetables, lean meat, and fish. As a result, the diet was lower in total fat and saturated fat, but contained equal amounts of n-6 and n-3 essential fatty acids. Linoleic acid (LA) is the major n-6 fatty acid, and alpha-linolenic acid (ALA) is the major n-3 fatty acid. In the body, LA is metabolized to arachidonic acid (AA), and ALA is metabolized to eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
351
2
20

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 553 publications
(386 citation statements)
references
References 61 publications
5
351
2
20
Order By: Relevance
“…High concentrations of dietary n-3 fatty acids reduce the activity of the enzyme in the n-6 pathway and the conversion of linoleic into ARA. The decrease in ARA content could be important for human health, as this acid is a precursor of some proinflammatory eicosanoids (Simopoulos, 2000). The egg cholesterol content significantly differed due to dietary fish oil treatment (Table 2).…”
Section: --mentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of dietary n-3 fatty acids reduce the activity of the enzyme in the n-6 pathway and the conversion of linoleic into ARA. The decrease in ARA content could be important for human health, as this acid is a precursor of some proinflammatory eicosanoids (Simopoulos, 2000). The egg cholesterol content significantly differed due to dietary fish oil treatment (Table 2).…”
Section: --mentioning
confidence: 99%
“…Introduction n-3-polyunsaturated fatty acids (n-3 PUFA) play an important role in human nutrition since they help to reduce the incidence of such lifestyle diseases as coronary artery diseases, hypertension and diabetes, as well as certain inflammatory diseases such as arthritis and dermatitis (Simopoulos, 2000). These diseases are an increasing problem in countries of the Middle East and North Africa, due to the dominance of animal fats and partially hydrogenated vegetable oils in the meals of the people of these countries.…”
mentioning
confidence: 99%
“…This strategy has proved to be viable and is currently applied to market eggs in several countries to improve the health image of eggs. Consumption of n-3 polyunsaturated fatty acids (n-3PUFA) has positive effects on health, including potential in prevention and treatment of cardiovascular diseases, diabetes, arthritis and certain types of cancer (Simopoulos, 2000). The balance between the two major types, n-6 and n-3PUFA, may also be crucial.…”
Section: Introductionmentioning
confidence: 99%
“…The balance between the two major types, n-6 and n-3PUFA, may also be crucial. According to the health point of view, Simopoulos (2000) stated that foodstuffs with an n-6/n-3 PUFA ratio of less than 4:1 are considered beneficial to -E-mail: tarkamin@gmail.com human health. Lewis et al (2000) and Kralik et al (2008) indicated a desirable ratio of n-6/n-3 PUFA of less than 4:1 in egg yolk lipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation